Pinus maximartinezii Rzed. (Pinaceae), first record for Durango, second locality for the species - González-Elizondo, Martha; González-Elizondo, M. Socorro; Ruacho-González, Lizeth; Molina-Olvera, Moisés (Instituto de Ecología, A.C., 2011)
Pinus maximartinezii Rzed. is recorded from southern Durango, the first known record in the wild in addition to the type locality in southern Zacatecas. Data about the new population are presented and the conservation implications for the species are discussed.